Xeno-free cryopreservation of adherent retinal pigmented epithelium yields viable and functional cells in vitro and in vivo - Britney O. Pennington (Nature Portfolio, 2021)
Abstract Age-related macular degeneration (AMD) is the primary cause of blindness in adults over 60 years of age, and clinical trials are currently assessing the therapeutic potential of retinal pigmented epithelial (RPE) cell monolayers on implantable scaffolds to treat this disease. However, challenges related to the culture, long-term storage, and long-distance transport of such implants currently limit the widespread use of adherent RPE cells as therapeutics. Here we report a xeno-free protocol to cryopreserve a confluent monolayer of clinical-grade, human embryonic stem cell-derived RPE cells on a parylene scaffold (REPS) that yields viable, polarized, and functional RPE cells post-thaw. Thawed cells exhibit ≥ 95% viability, have morphology, pigmentation, and gene expression characteristic of mature RPE cells, and secrete the neuroprotective protein, pigment epithelium-derived factor (PEDF). Stability under liquid nitrogen (LN2) storage has been confirmed through one year. REPS were administered immediately post-thaw into the subretinal space of a mammalian model, the Royal College of Surgeons (RCS)/nude rat. Implanted REPS were assessed at 30, 60, and 90 days post-implantation, and thawed cells demonstrate survival as an intact monolayer on the parylene scaffold. Furthermore, immunoreactivity for the maturation marker, RPE65, significantly increased over the post-implantation period in vivo, and cells demonstrated functional attributes similar to non-cryopreserved controls. The capacity to cryopreserve adherent cellular therapeutics permits extended storage and stable transport to surgical sites, enabling broad distribution for the treatment of prevalent diseases such as AMD.